Al-Sunnah Dalam Kurikulum Sekolah Agama Petang Perlis (SAPPs) Majlis Agama Islam Dan Adat Istiadat Melayu Perlis (MAIPs) - Hazman Hassan; Mohammad Isyraf Ishak; Mohd Kasturi Nor Abd Aziz; Mohd Nazim Mohd Noor; Nidzamuddin Zakaria (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies